2015
DOI: 10.1080/10669868.2014.993008
|View full text |Cite
|
Sign up to set email alerts
|

Liability of Foreignness of Emerging Market Firms: The Country of Origin Effect on Russian IT Companies

Abstract: Foreign subsidiaries are considered to be at a disadvantage compared to domestic firms in foreign markets. The liability of foreignness (LOF) concept was first attempted in order to address the issue of these disadvantages. Although internationalization of emerging market firms (EMFs) is a very hot topic, there is very little research of LOF of EMFs. In this article, we investigate the sources of LOF and determine the extent of the country-of-origin (COO) effect on Russian IT firms. We also discuss how Russian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…Importantly, while the study is concerned with Chinese firms, our propositions and the framework should apply to emerging market multinationals in general. It is because those firms often struggle with the disadvantages associated with their COO, causing a high liability of origin (Panibratov, ; Ramachandran & Pant, ). After all, they are not only “new” to host countries, in which case they will be subject to strong stereotypical judgment regarding COO, but also lack firm‐level attributes such as a well‐known brand to alleviate the COO effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, while the study is concerned with Chinese firms, our propositions and the framework should apply to emerging market multinationals in general. It is because those firms often struggle with the disadvantages associated with their COO, causing a high liability of origin (Panibratov, ; Ramachandran & Pant, ). After all, they are not only “new” to host countries, in which case they will be subject to strong stereotypical judgment regarding COO, but also lack firm‐level attributes such as a well‐known brand to alleviate the COO effect.…”
Section: Resultsmentioning
confidence: 99%
“…As prior research has shown, an individual's tendency to rely on COO as an important cue in the evaluation of a foreign entity will be stronger when he or she has little familiarity with the products (Ahmed & d'Astous, ) and other information about the entity is absent or inadequate (Strutton et al, ). Panibratov's () recent study, for example, provides evidence that Russian firms operating in Europe struggle with the disadvantageous COO effect, which leads to the liability of foreignness (Zaheer, ).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Indeed, there is a widespread view that the label “Made in Russia” has a negative connotation internationally, particularly in technology‐intensive industries (Panibratov, ). Our respondents stated that they often face considerable mistrust towards their products and company in general.…”
Section: Results Of Data Analysismentioning
confidence: 99%
“…Furthermore, we find that impact of the liability of origin has a dual nature. On one hand, it represents an obstacle for international competitiveness and on the other hand, it motivates Russian firms “to try harder.” To overcome this liability, Russian firms have to develop creative approaches of starting business abroad, particularly in developed countries (Panibratov, ). Once the trust is gained, the effect of this liability becomes marginal, if existent at all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation